As narrativas do desejo: procedimentos criativos e comunicativos de Pedro Almodóvar - Jaime-Smith, Daniela (2020)
This research investigates the processes and procedures of creation from the Spanish filmmaker Pedro Almodóvar, reflecting about the dramaturgical weaving created by the filmmaker in the process of building his poetical project, observing the procedures that involve his thinking and his practice as a screenwriter and director, to thereby reflect about creative processes of authorship and communication. The hypothesis is that his poetical project is built through the selection and transformation of thematic and aesthetic elements present in his own work and the work of other authors, whose works affected his sensitivity, causing themes and characters to be repeated under different perspectives over time, creating a universe marked by the constant reinvention of texts and films in order to create his own filmic systems. This study was made using interviews of the director and the analysis of some of his films, principally “The flower of my secret” and “All about my mother”, which maintain a dramaturgical relationship, once that in the “The flower of my secret” there are scenes as generating matrices, triggers of the creation process for the film “All about my mother”, an enlarged embryo of such scenes. From the theories of Cecilia Almeida Salles about the creation process which is based on C.S. Pierce' semiotics and proposes dialogues with authors such as Edgard Morin, Vincente Colapietro, Zygmunt Bauman, and Pierre Musso, we reflected on the issues involving creative processes. Robert Mckee's theory of screenplay writing was used to analyze the creation of dramatic structures in both films. Edgar Morin's thinking collaborated on the reflection of related aspects about the relation between culture and society, as well as in the reflection on the qualities and characteristics of cinema. Michel Foucault's theory was used to think about issues related to authorship. The methodology consisted of an analysis of Almodóvar's filmography, establishing a relationship with his interviews, to thereby generate the investigation and the reflection about the creation process based on the theory described above